Estimating extreme cancellation rates in life insurance - Francesca Biagini; Tobias Huber; Johannes G. Jaspersen; Andrea Mazzon (Journal of Risk and Insurance, 2021)
This paper assesses the risk of a mass lapse event in life insurance. The rarity of the event and the complexity of policyholder behavior make the risk assessment of such a scenario difficult. Using a simulation study, we evaluate how different estimation methods can assess the risk of this scenario, using panel data at the company level. We then use the best-performing method to estimate the probability distribution function of a mass cancellation event in the United States and Germany. We identify dependencies of the event on company and country characteristics, which have not been taken into account by regulating agencies. We also find that the current mass lapse scenario in Solvency II has no empirical foundation for the German market. We show that an empirically valid scenario leads to a significantly lower solvency capital requirement for the average German life insurer.
Keywords: 330; dynamic peaks over threshold; extreme value theory; life insurance; mass cancellation